STUDY ON CRITICAL CTOD OF BIG-THICKNESS AND HIGH-STRENGTH STEELS - XIA ZiYu; MIAO ZhangMu; MA Tao; CHEN Gang; PENG Sheng (Jixie qiangdu)
As one of the essential criteria of assessment to welding toughness,CTOD（ Crack tip opening displacement） is widely applied in engineering.The research on critical CTOD of big thickness and high strength steels has been a hot issue,therefore the theoretical research in China lags behind its overseas.The present paper takes the single edge fatigue precrack of CTOD specimen as a flaw based on the technical route of the British Standard 7910-2005,which is "Guide to methods for assessing the acceptability of flaws in metallic structures".In the meanwhile,make the grading assessments of the HAZ of the60 mm thick EQ70 steel welded joints,combining the results of the CTOD tests.The CGHAZ microstructures of EQ70 steel welded joints has been analyzed by SEM.The assessments on welded joints of EQ70 show that the CTOD values are in the acceptable range.And there are some fine microstructures good for the toughness of the welded joint.This method provides a useful guidance in researches of critical CTOD.